Antimicrobial Cathelicidin Peptide LL-37 Inhibits the LPS/ATP-Induced Pyroptosis of Macrophages by Dual Mechanism - Hu, Zhongshuang; Murakami, Taisuke; Suzuki, Kaori; Tamura, Hiroshi; Kuwahara-Arai, Kyoko; Iba, Toshiaki; Nagaoka, Isao (PLOS ONE, 2014)
Pyroptosis is a caspase-1 dependent cell death, associated with proinflammatory cytokine production, and is considered to play a crucial role in sepsis. Pyroptosis is induced by the two distinct stimuli, microbial PAMPs (pathogen associated molecular patterns) and endogenous DAMPs (damage associated molecular patterns). Importantly, cathelicidin-related AMPs (antimicrobial peptides) have a role in innate immune defense. Notably, human cathelicidin LL-37 exhibits the protective effect on the septic animal models. Thus, in this study, to elucidate the mechanism for the protective action of LL-37 on sepsis, we utilized LPS (lipopolysaccharide) and ATP (adenosine triphosphate) as a PAMP and a DAMP, respectively, and examined the effect of LL-37 on the LPS/ATP-induced pyroptosis of macrophage-like J774 cells. The data indicated that the stimulation of J774 cells with LPS and ATP induces the features of pyroptosis, including the expression of IL-1β mRNA and protein, activation of caspase-1, inflammasome formation and cell death. Moreover, LL-37 inhibits the LPS/ATP-induced IL-1β expression, caspase-1 activation, inflammasome formation, as well as cell death. Notably, LL-37 suppressed the LPS binding to target cells and ATP-induced/P2X7-mediated caspase-1 activation. Together these observations suggest that LL-37 potently inhibits the LPS/ATP-induced pyroptosis by both neutralizing the action of LPS and inhibiting the response of P2X7 to ATP. Thus, the present finding may provide a novel insight into the modulation of sepsis utilizing LL-37 with a dual action on the LPS binding and P2X7 activation.